THE APPLICATION OF ACTIVITY-BASED COSTING (ABC) AND JOB ORDER COSTING (JOC) AT WISATA BAHARI RESTAURANT MANADO - Ramintang, Jessica; Pangemanan, Sifrid (Universitas Sam Ratulangi, 2016)
ABC is used to determine more accurate product costs by tracing activities required, especially for the purpose of decision making. ABC can show to management about the high cost of low-volume products. Smokie Crab and Grilled Squid from Wisata Bahari Restaurant, Manado, are the sample. Â The purpose of this research is make more accurate calculation of the cost, which can provide information on the cost of production is more clear for owner of Wisata Bahari Restaurant Manado, so as to obtain the cost of goods sold better in the competition. There are several ways to determine the cost of goods sold as cost calculation system based on order (job order costing), cost calculation system based on process (process costing), activity-based costing system (ABC), determining the selling price of normal (normal pricing), and others. JOC is to calculate the cost of goods selling by any order, whether raw materials, labor, and overhead. While ABC system uses activity as the pricing of goods selling. Of these activities, the overall total cost charged to each product. Between ABC and JOC calculation for Smokie Crab and Grilled Squid, there are differences between the selling price. For smokie crab, better if Wisata Bahari Restaurant using ABC calculation. But for grilled squid, JOC calculation. Keywords: activity-based costing, job order, selling price